On Grade Option Choice and Grade Performance Expectation When Instruction Goes Virtual – The Role of Peers at a Distance - Arnab K. Basu; Nancy H. Chau; Yudi Wang (Institute of Labor Economics (IZA), 2025)
Campus closures due to COVID19 created uneven student-level exposures to the challenges of home-based virtual learning. Using university administrative data, and exogenous class-level differences in pre-pandemic on-campus housing assignments for parallel trend validation, this paper unpacks student-by-course variations in grade expectations using within-semester switches in grade option choice as a lens. We find causal evidence that distance from campus and internet access affected grade option choices in select student groups (female, non-URM, non-STEM). By tracking access to friends at the student-course level using administrative records, we find that within-class peer support can offset learning challenges even in virtual environments.
Keywords: I20; I29; 330; satisfactory/unsatisfactory grade option; COVID-19; distance education; learning outcomes